The Power of Imagery: the Visual Language of the Ukrainian SSR Local Newspapers of the Early 1930s - Kostiv, Mykhailo; Soproniuk, Tetiana (Knygotyra, 2025)
Along with textual articles, the local press of the Ukrainian SSR in the early 1930s often contained visual elements, which, despite their poor quality, had enormous propagandistic potential. These newspapers were predominantly targeted at the rural population and communicated with their audience in a direct and prescriptive manner. Moreover, because of strong censorship, they were never illustrated by images that would reflect the actual socio-economic problems and thus compromise the Soviet regime. Therefore, the aim of this article is to define the major types of images that were published in the raion (i.e., province) level newspapers of the Ukrainian SSR and explore the messages they conveyed. In particular, by using the animal code and referring to well-known idioms, caricatures shaped the image of both domestic (‘kulaks’, priests, etc.) and foreign (Western capitalist countries) enemies. In contrast, numerous portraits of the communist chiefs and the most productive workers, both male and female, constructed the gallery of role models for the readers. At the same time, the basis of the newspapers’ visual content was the staged group portraits and photographs of people at work and industrial landscapes, depicting an idealized ‘communist paradise’ – a pseudo-reality of rapid and successful economic changes. The newspapers also utilized the images of Soviet and Western weapons and/or military personnel, trying to keep the readers in a state of readiness for possible military aggression without simultaneously causing panic. In addition, monumental, complex, and multi-layered illustrations, similar to traditional political posters, were often included in the press issues devoted to the State holidays. Many of them featured the images of a perfect Soviet man or woman, and embodied the greatness of the USSR. Finally, the emotional, simple, and straightforward visual language of the Ukrainian SSR raion press aimed to mobilize the population for selfless work “in favor of their socialist Motherland” and actively support the Soviet Government’s policies.
Keywords: local press; Ukrainian SSR; propaganda; visual language; photography; newspaper; Holodomor